2007
DOI: 10.1007/s10658-007-9242-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of citrus bacterial canker strains in Korea by host range, rep-PCR fingerprinting and 16S rDNA analysis

Abstract: New Xanthomonas isolates causing citrus bacterial canker in Korea were differentiated primarily on the basis of host range by comparison with reference strains. The new isolates were pathogenic to Citrus sinensis, C. paradisi, C. limon and C. unshiu and formed crater-like canker on the plants; this indicated that they were X. axonopodis (X.a.) pv. citri A types. Molecular characterization using rep-PCR fingerprinting and 16S rDNA sequence analysis was also performed. Cluster analysis by combining the band patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Moreover, the analysis of 16S rDNA sequences did not give any discrimination between Saudi strains. Our results corroborate with the previous research that showed 16S rDNA sequences of different pathotypes of Xanthomonas causing citrus canker disease (A, B and C) were Xcc with a similarity of 99% (Lee et al, 2008). Fox et al (1992) reported that the 16S rDNA gene was considered unsuitable for discriminating and identifying closely related strains due to the high levels of sequence similarity in this region.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the analysis of 16S rDNA sequences did not give any discrimination between Saudi strains. Our results corroborate with the previous research that showed 16S rDNA sequences of different pathotypes of Xanthomonas causing citrus canker disease (A, B and C) were Xcc with a similarity of 99% (Lee et al, 2008). Fox et al (1992) reported that the 16S rDNA gene was considered unsuitable for discriminating and identifying closely related strains due to the high levels of sequence similarity in this region.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies considered primarily the usefulness of PFGE, AFLP, or rep-PCR markers in terms of their abilities to determine genetic relationships between Xanthomonas pathovars that are pathogenic to citrus and X. citri pv. citri pathological variants (16,19,39,44,68).…”
Section: Discussionmentioning
confidence: 99%
“…The rep-PCR dendrogram consisted of two main clusters with 51% genetic similarity among the rest of the isolates. In previous studies, this amount of genetic diversity was seen only amongst different species (formerly different strains) of CBC inducing bacteria (Cuberto and Graham 2002;Lee et al 2007). The other cluster was divided into five groups, containing the strains from two other closer states being surveyed.…”
Section: Resultsmentioning
confidence: 87%
“…Only the reproducible bands ranging from 0.2 to 3 kb were scored. Since combined analysis of rep-PCR primers showed a significant increase in differentiation capacity in other works (Trindade et al 2005;Lee et al 2007), combined data generated from two sets of primers were combined and then subjected to analysis. To estimate the genetic relationship among the strains, the similarity coefficient for pairs of isolates was calculated with Dice's coefficient index (Dice 1945).…”
Section: Discussionmentioning
confidence: 99%